If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y = 12(y + 6) Reorder the terms: 13y = 12(6 + y) 13y = (6 * 12 + y * 12) 13y = (72 + 12y) Solving 13y = 72 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 13y + -12y = 72 + 12y + -12y Combine like terms: 13y + -12y = 1y 1y = 72 + 12y + -12y Combine like terms: 12y + -12y = 0 1y = 72 + 0 1y = 72 Divide each side by '1'. y = 72 Simplifying y = 72
| 900=3n+3 | | 14+7x=91 | | 6x-11=67 | | (2x+3y)-5=6x-8y | | -8n+4(1+5n)=-6n+4 | | 9y=6y+12 | | 4(x-9)=-26 | | 4/x-5=-18/x+6 | | 2(a+9)=36.4 | | -4y+10x=36 | | 3x+2/x-1=8 | | 16.2=7c-9 | | 5x+8/2=14 | | 6e-2=17.8 | | 40x=60 | | 12(k+4)=60 | | -8+p=31 | | 2(x-5)+4=2x+3 | | 2.5=s/7 | | 5y-9+y+33=7y+30-4y | | 3x+1.7=9.2 | | -4/15=x-7/12 | | 5/8=y+1/8 | | a+6.6=4.9 | | 12s^2-9s= | | -3x^2+12x+1=0 | | 14x^2-15x-9=0 | | 5r^2+3r+3=0 | | 3c-200+1c=2c+2c-150-50 | | 5.2z=31.2 | | 2x^2+2-3=0 | | 6(x-9)=5(x-9) |